The Influence of Islamic Financial Behavior and Pocket Money on Online Shopping Decisions of Students at the State Islamic University of North Sumatra - Nurhabibi, Elsa; Ahmad Syakir; Muhammad Ikhsan Harahap (Amkop Management Accounting Review (AMAR), 2025)
This study analyzes the influence of Islamic Financial Behavior and pocket money on the online shopping decisions of students at State Islamic University of North Sumatra (UINSU). The rapid development of e-commerce has transformed consumption behavior; however, this phenomenon has also led to a decline in revenue for conventional traders. Students' online shopping decisions are not only influenced by the ease of platforms but also by individual financial behavior and financial capacity. Islamic Financial Behavior, based on sharia principles (avoiding wastefulness and prioritizing needs), and pocket money as the main determinant of students' purchasing power, are suspected to play a significant role. This associative quantitative research involved 100 UINSU student respondents selected using the Slovin formula. Data were collected through questionnaires and analyzed using multiple linear regression (IBM SPSS Statistics 25). The t-test results indicate that Islamic Financial Behavior (t=4.279; p=0.000) and pocket money (t=9.306; p=0.000) individually have a significant effect on online shopping decisions. The F-test (simultaneous) confirms that both variables collectively have a significant effect (F=85.903; p=0.000). The coefficient of determination (R-square) of 0.639 (63.9%) shows the contribution of both variables in explaining online shopping decisions, while the remaining 36.1% is explained by other factors. These findings underscore the importance of Islamic financial principles and money management in shaping prudent online shopping decisions among Muslim students.